2009
DOI: 10.1007/s11325-009-0273-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a modified mandibular advancement device for a totally edentulous patient with severe obstructive sleep apnea

Abstract: This clinical case shows fabrication method and treatment efficacy of a modified MAD, which is aiming to displace bulky masseter muscles laterally, to provide more space for tongue on totally edentulous patient with severe OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There are few studies in the literature that address the treatment of edentulous individuals using a MAD, and those that do exist are limited to case reports. The majority of the studies support the device on the alveolar ridge [12–14] or on the tongue retainer flange [15] . Others build the device over a complete upper prosthesis [16] or on complete upper and lower prostheses [17] .…”
Section: Discussionmentioning
confidence: 97%
“…There are few studies in the literature that address the treatment of edentulous individuals using a MAD, and those that do exist are limited to case reports. The majority of the studies support the device on the alveolar ridge [12–14] or on the tongue retainer flange [15] . Others build the device over a complete upper prosthesis [16] or on complete upper and lower prostheses [17] .…”
Section: Discussionmentioning
confidence: 97%
“…The literature revealed a fewer numbers of therapeutic strategies used in the treatment of edentulous patients with OSA [35, 7, 8]. This paper describes the clinical procedure of fabrication of a modified MAD for edentulous lower jaw patient with OSA and evaluates these results.…”
Section: Discussionmentioning
confidence: 99%
“…Kurtulmus and Cotert [3] described a new functional splint combining a MAD and a TRD. Piskin et al [5] reported modified MAD which displaces bulky masseter muscles laterally to provide more space for the tongue in edentulous patients. Arisaka et al [7] indicated that just wearing the complete dentures during sleep improved the AHI in some edentulous OSA patients by restoring the vertical mandibular position without change in the horizontal mandibular position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations